Violent computer games and their effects on state hostility and physiological arousal - Arriaga, P.; Esteves, F.; Carneiro, M. P.; Monteiro, M. B. (Aggressive Behavior, 2006)
An experimental study was conducted to investigate the impact of violent computer games on state hostility, state anxiety and arousal. Participants were undergraduate students, aged from 18 to 25 years. Before the experimental sessions, participants filled in self-report measures concerning their video game habits and were also pre-tested for aggressiveness and trait anxiety. Physiological responses (heart rate and skin conductance) were measured during the experiment. After playing, information about state hostility and state anxiety was collected. The results showed that participants who played the violent game reported significantly higher state hostility, and support the assumption that an aggressive personality moderates the effect of playing a violent game on state hostility.